Design of electrically conducting polymer hybrid composites based on polyvinyl chloride and polyethylene - Kuryptya, Yaroslav; Sova, Nadiya; Savchenko, Bohdan; Slieptsov, Aleksander; Plavan, Viktoriia (Eastern-European Journal of Enterprise Technologies, 2016)
Interest to electrically conducting polymer composite materials in recent times has grown considerably, which is associated with the design of new branches of science and technology. The existing analogues are different in the complexity of production and high cost. One of the ways of solving the problem may be designing polymer composite materials with a combined filler. The research was carried out on creating electrically conducting hybrid polymer composites, based on emulsion polyvinyl chloride and polyethylene, using fillers of varying nature and dimensions. We studied the dependence of electrical conductivity of mono and binaryfilled polymer composites on the type and content of fillers. It was found that the binary filling allows designing electrically conducting polymer composites, which are more promising economically compared to monofilled ones. We defined physical and mechanical characteristics: tensile strength and relative elongation at break of obtained polymer composites. A method to improve them was proposed by introduction of a compatibilizer – graftpolymer of polyethylene with maleic anhydride. Depending on the value of the electrical conductivity, polymer hybrid composites can be used for: at a value of of elecrical conductivity 10–4–10–7Cm/cm as antistatic materials; at 101–10–4 Cm/cm – as scattering antistatic materials, at 101– 104 Cm/cm as currentconducting materials.